Art at the limits of perception: the aesthetic theory of Wolfgang Welsch - Carroll, Jerome (2004)
This thesis presents and critically assesses the aesthetic theory of the contemporary German philosopher Wolfgang Welsch, in particular his ideas of the intersection of philosophical aesthetics and contemporary culture. The three aspects of his ideas which frame this discussion and which I present in the first chapter are his project for reconfiguring aesthetics as a study of sensory perception, his characterisation of postmodern culture as aestheticised, and his conception of a new focus for aesthetics, the anaesthetic or imperceptible. Welsch's ideas intersect with several key issues in philosophical aesthetics which I outline in the second chapter, namely the status of the sensory and its relationship to the quality of indeterminacy, the subjective and cognitive nature of the aesthetic experience, the idea of the aesthetic as an epistemological ground that is in some way distinct from rational or conceptual knowledge, and finally the aesthetic characterised as an essentially modernist quality of defamiliarisation. The interlocutors here are Alexander Baumgarten, Kant and the Russian Formalists. This is followed in the third chapter by a more focussed discussion of Welsch's ideas on the sublime, a crucial aesthetic category which offers a theoretical background to his ideas on anaesthetics. Welsch reads the sublime as pivotal to the aesthetics of Adorno and the aesthetic thinking of Lyotard, and the main argument in this chapter compares the postmodern fascination with diversity or heterogeneity as values in themselves with a more ideologically informed conception of the cognitive and social function of modern and postmodern art as challenging existing modes of perception. I also read the limit experience of the sublime as a model for the modernist aesthetic of defamiliarisation. A critical discussion of Welsch's own variant of the sublime, the anaesthetic, follows in chapter four. The key issues here are the tensions between Welsch's disparate uses of the term, the ideological implications of each variant, and to what extent each allows a re-engagement of indeterminacy with everyday culture, or tends towards a more autonomous aesthetic. The final two chapters apply Welsch's ideas and the issues raised to examples of art, specifically drama, that operates at the limits of perception. The aim here is to assess whether Welsch's sensory terms offer the articulation of art and contemporary culture, or whether with some modifications they might. An overarching concern of the thesis is to distinguish between the transcendental significance of the aesthetic and its more marginal validity as cultural intervention.